Infection Dynamics of Opisthorchis viverrini Metacercariae in Cyprinid Fishes from Two Endemic Areas in Thailand and Lao PDR - Namsanor, Jutamas (Am J Trop Med Hyg, 2020)
The infection dynamics of Opisthorchis viverrini metacercariae was analyzed in cyprinid fish from endemic areas in Mukdahan Province, Thailand, and Khammouane Province, Lao PDR. The fish were collected during the cool-dry (November–February), hot-dry (March–May), and rainy (June–October) seasons in 2017. They were examined by the digestion method, and the infection status was statistically analyzed by study area, season, and fish size. The prevalence (no. of fish positive/no. of fish examined × 100) and metacercarial intensities (no. of metacercariae detected/no. of fish positive) of O. viverrini in both study areas depended on season, being high in the cool-dry season and varying in the hot-dry and rainy seasons. In Mukdahan Province, the average prevalence was 18.3% (range 11.0–46.7%, n = 420) and the intensity was 4.07 ± 5.86 cysts/fish (mean ± SD), whereas in Khammouane Province, the prevalence was 51.9% (range 9.1–70.6%, n = 673) and the intensity was 6.67 ± 12.88 cysts/fish. Among the cyprinid fish species examined, the infection was associated with fish body size and predominantly found in Hampala dispar (86.5%), Cyclocheilichthys armatus (73.2%), and Puntius brevis (42.7%). The distribution of O. viverrini metacercariae in fish was skewed, with most of the fish having a low worm burden with an average of four to six cysts/fish. The findings that seasonality, sampling locality, fish size, and species of fish play roles in the risk of O. viverrini infection imply that these host and environmental factors are important for the transmission dynamics and control of O. viverrini.